IMPLEMENTASI KEBIJAKAN PEMINDAHAN IBUKOTA KABUPATEN MALANG (Studi Pada Implementasi PP. No 18 Tahun 2008 Tentang Pemindahan Ibukota Kabupaten Malang Ke Kecamatan Kepanjen) - Eka Ayu Intan Permatasari (Jurnal Administrasi Publik, 2015)
Abstract: Policy Implementation Transfer of the Capital Regency Malang " (A Study on Implementation of PP. No. 18 of 2008 About Transfer of Capital Regency Malang to Kepanjen District). The existence of Capital Regency Malang who had been in the city of Malang is considered less consistent with the policy of Malang who actively doing development in various fields. Therefore, should be move Capital Regency Malang. From the research results studies, DistrictÂ  Kepanjen judged worthy and qualified to serve as the capital Regency Malang. Based on Government Regulation No. 18 of 2008, then implemented transfer of the Capital Regency Malang gradually. District Kepanjen enactment as the Capital Regency Malang for make Kepanjen as a center of economic development and governance. The implementation of the transfer of the Capital Regency Malang to Kepanjen directed by Local Regulation No. 3 of 2010 About Spatial Plans of Malang Regency. To support the success of implementation transfer of the Capital Regency Malang has the aspect of communication between the government and relevant actors, availability aspects of land that can support the implementation transfer of the Capital Regency continuity, aspects of the attitude of the executive in implementing the policy and implementation aspects of the bureaucratic structures that transfer of the Capital Regency Malang properly fulfilled.However, some factors are constraining the implementation such the lack of commitment between irrigation department and Cipta Karya departments in directing existing development and lack of budget for implementation transfer of the Capital Regency. Keyword: Policy Implementation, Capital Regency Abstrak: Implementasi Kebijakan Pemindahan Ibukota Kabupaten Malangâ€(Suatu Studi Pada Implementasi PP. No 18 Tahun 2008 Tentang Pemindahan Ibukota Kabupaten Malang Ke Kecamatan Kepanjen). Keberadaan Ibukota yang Â saat itu bertempat di wilayah Kota Malang kurang selaras dengan kebijakan yang sedang melakukan pembangunan di berbagai bidang. Oleh karena itu, Â perlu dipindah Ibukota Kabupaten Malang. Dari studi hasil lapangan secara keseluruhan, KecamatanÂ  Kepanjen dinilai layak dan memenuhi syarat untuk dijadikan Ibukota Kabupaten Malang. Berdasarkan PP No 18 Tahun 2008 maka dilaksanakan pemindahan Ibukota Kabupaten secara bertahap. DitetapkannyaÂ Â Â  Kepanjen sebagai Ibukota Kabupaten Malang menjadikan Kepanjen sebagai pusat pengembangan ekonomi dan pemerintahan. implementasi pemindahan Ibukota Kabupaten Malang ke Kepanjen diarahkan berdasarkan Perda No 3 Tahun 2010 Tentang Rencana Tata Ruang Wilayah Kabupaten Malang. Untuk mendukung keberhasilan. implementasi pemindahan Ibukota Kabupaten Malang telah memperhatikan aspek komunikasi antara pemerintah dengan aktor terkait, aspek ketersedian lahan yang dapat mendukung keberlangsungannya implementasi pemindahan Ibukota Kabupaten , aspek sikap para pelaksana dalam melaksanakan kebijakan dan aspek struktur birokrasi sehinggaÂ  implementasi pemindahan Ibukota Kabupaten Malang terlaksanakan dengan baik. Namun, dalam implementasinya masih terdapat faktor penghambat antara lain adalah kurangnyaÂ  komitmenÂ  antara dinas pengairan dan dinas cipta karya dalam mengarahkan pembangunan yang ada dan minimnya anggaran untuk pelaksanaan pemindahan Ibukota Kabupaten. Â  Kata kunci: Implementasi Kebijakan, Ibukota Kabupaten